Sexual agency, risk and vulnerability: a scoping review of young Indigenous Australians' sexual health. (21st October 2017) - Bell, Stephen; Aggleton, Peter; Ward, James; Maher, Lisa
ABSTRACT: This review of qualitative research examining young Indigenous Australians' sexual health highlights the profoundly social nature of young people's sexual lives. Nineteen peer reviewed published papers were identified for inclusion. Findings reveal efforts made by some young Indigenous Australians to control their sexual lives, mitigate risk and maintain their sexual health. The review identified factors which are conducive to sexual health risks and vulnerability, including incomplete knowledge about STIs and safer sexual practices; gossip and ridicule concerning sexual activity and its consequences; damaging expectations about male prerogatives with respect to sexual relationships; limited inter-generational communication about sexual health issues; inadequate school-based sexual health education; and tensions between Indigenous and biomedical explanations of sexual health issues. Future research priorities include a focus on young Indigenous people in cities and towns across Australia, and in regional and remote settings in New South Wales and Victoria; understanding how Indigenous cultural values support young people's sexual health; young men's sexual and service-based practices; and the experiences of same-sex attracted and gender diverse youth. This research would inform the design and delivery of culturally safe and acceptable sexual health services and programmes, underpinned by an understanding of factors in young Indigenous Australians' everyday sexual lives.